Título Padrão - Barak, Jim (Revista de Ciências Sociais, 2020)
Historians frequently remark in private conversation that while philosophers may demolish historical relativism regularly in theory, it remains a compelling and cogent account of the practice of historical writing. Historical relativism seems to be one of those cases where the problem involves the phenomenon of "Its all right in practice, but will it work in theory?"